Investigation of Tribological Performance of Ti:WS2/PFPE Composite Lubricating System Under Proton Radiation - Jian Liu; Zhen Yan; Junying Hao; Weimin Liu (Lubricants)
The tribological performance of PFPE oil and the Ti:WS2/PFPE composite lubricating system with different oil amounts was investigated under a proton radiation (PR) irradiation environment. After PR irradiation, PFPE molecules occurred during cross-linking and a polymerization reaction and formed a volatile small molecular compound, which deteriorates the tribological performance of the Ti:WS2/PFPE system. The tribological properties of the Ti:WS2/PFPE system rely strongly on oil amount. For an unirradiated Ti:WS2/PFPE system, the amorphous layer of transfer film near the sliding contact area was converted into a well-defined crystalline WS2 layer with a (002) plane induced by the friction process. After PR irradiation, the transfer film became thicker and showed a wholly amorphous structure due to the difficulty in preventing the entrance of O and showed no reorientation with induced friction.